Potensi Sinar Matahari Pagi Untuk Menurunkan Kadar Gula Darah Penderita Diabetes - Atyanti Isworo (Journal of Bionursing, 2020)
Background: Sunlight contains ultraviolet A (UV A) and ultraviolet B (UV B). UV B is able to produce vitamin D. Vitamin D is believed to increase insulin sensitivity and secretion. Therefore the purpose of this study is to discover the efficacy of morning sunlight on the blood sugar of diabetic patients.Method: This study is a quasi-experiment with control group design, which was conducted in the working area of North Purwokerto Puskesmas I and II. A total of 40 respondents were divided into 2 groups, each group of 20 respondents were involved in this study, using consecutive sampling technique. The inclusion criteria in this study are (1) diabetics patients using oral hypoglycemic drugs, (2) have fasting blood glucose level ? 126 mg/dL, (3) aged ? 40 years, (4) have no chronic complication of diabetes (kidney disease, retinopathy, nephropathy, and neuropathy), (5) willing to be a respondent, (6) had not eaten for at least 8 hours when the study was conducted, (7) participated in all sessions of the research; while the exclusion criteria: (1) have an obesity BMI, (2) under a severe stress. Procedure: The intervention group was asked to sunbathe in the morning sunlight for 20 minutes, between 06:00-09.00. During this sunbathing session respondents sat and wore one layer of clothing (without wearing a jacket) and with materials that easily absorb sweat. This activity was carried out 5 times in a row. On the fifth day, respondents measured their fasting blood glucose level again. The statistical analysis used was the Wilcoxon and Mann-Whitney Test.Result: The result showed that there were significant differences in the mean fasting blood glucose level before and after treatment in the intervention group (p = 0.000), but no differences were found in the control group (p = 0.881). Furthermore, using the Mann Whitney test, there were significant differences in fasting blood glucose after the treatment between the two groups (p=0,000)Conclusion: Morning sunlight has the potential to reduce fasting glucose level in diabetic patients. Further research is needed on morning sunlight for diabetics by considering several confounding variables.